Cover Feature: Direct Arylation of Dipyrrolonaphthyridinediones Leads to Red‐Emitting Dyes with Conformational Freedom (Chem. Eur. J. 4/2018). Issue 4 (13th November 2017) - Sadowski, Bartłomiej; Rode, Michał F.; Gryko, Daniel T.
Abstract : Dipyrrolonaphthyridinediones that possess two aryl substituents at positions 3 and 9 can be prepared directly from parent heterocycle by direct arylation. Although benzene rings in the new dyes are only weakly coupled with the key chromophore, the dihedral angles are much smaller in the excited state. As a result, fluorescence is shifted from green–yellow to the far‐red/NIR region. The photophysical properties can be controlled by altering the steric and electronic character of the peripheral group. More information can be found in the Full Paper by M. F. Rode, D. T. Gryko et al. onpage 855 .